2019
DOI: 10.32479/irmm.8530
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Competence and Ship Crew Discipline on Performance Pt. Myclin Express Offshore

Abstract: Every shipping company needs competent and qualified ship crews in carrying out activities in order to help the company achieve company performance. In addition to supporting crew competence, another factor which is no less important is the discipline of the crew itself. But in reality many crew members do not meet the standards and qualifications given by the company, so they do not provide maximum performance, as a result the achievement of company performance is very low. Solving problems related to this ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
1
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 11 publications
0
4
1
2
Order By: Relevance
“…The results of this study are not in line with that expressed by Wyatt in (Achmad, 2003) states competence is the combination of skills, knowledge, and behavior that can be observed and applied critical to the success of an organization and achievement work and employee's personal contribution to the organization. Thus disagrees with the results of research conducted by (Khattak et al, 2016), (Tehseen et al, 2018), (Meswantri & Awaludin, 2018), (Alexandri et al, 2019), (Malau et al, 2019) which produced a study that variable competence positive and significant effect on employee performance.…”
Section: Influence Of Competence On Organizational Commitment At Pt contrasting
confidence: 58%
See 2 more Smart Citations
“…The results of this study are not in line with that expressed by Wyatt in (Achmad, 2003) states competence is the combination of skills, knowledge, and behavior that can be observed and applied critical to the success of an organization and achievement work and employee's personal contribution to the organization. Thus disagrees with the results of research conducted by (Khattak et al, 2016), (Tehseen et al, 2018), (Meswantri & Awaludin, 2018), (Alexandri et al, 2019), (Malau et al, 2019) which produced a study that variable competence positive and significant effect on employee performance.…”
Section: Influence Of Competence On Organizational Commitment At Pt contrasting
confidence: 58%
“…This conclusion is also supported by the results of (Trismiyanto, Sule, Joeliaty, & Yunizar, 2018) stated that competence in the field of entrepreneurship has a positive and significant effect on performance. Likewise, the results of (Alexandri, Pragiwani, & Yuswardi, 2019) revealed that competence had a positive and significant effect on performance at the Criminal Investigation Police and (Malau et al, 2019) in his research stated competence had a positive and significant effect on performance. Based on the above research the following hypotheses can be formulated:…”
Section: Concepts and Hypothesesmentioning
confidence: 92%
See 1 more Smart Citation
“…Sebuah perusahaan meningkatkan efektivitas dan kinerjanya dengan tenaga kerja terampil perusahaan. Jadi perusahaan fokus dan berinvestasi pada program Pelatihan & Pengembangan yang efektif untuk efektivitas organisasi (Malau et al, 2019). Uang yang dikeluarkan untuk kegiatan Pelatihan & Pengembangan dianggap sebagai investasi hanya ketika Pelatihan & Pengembangan memenuhi tujuan peningkatan kinerja tenaga kerja yang dimaksudkan (Dessler, 2014) Kebutuhan tersebut dapat muncul pada tiga tingkatan a) pada tingkat organisasi, berdasarkan perencanaan strategis, kebutuhan bisnis dan tujuan serta sasaran organisasi, b) pada tingkat individu, berdasarkan tingkat kinerja karyawan, kebutuhan yang diperlukan keterampilan dan peningkatan pengetahuan, c) pada tingkat operasional, pekerjaan atau tugas yang akan diberikan kepada karyawan.…”
Section: Langkah-langkah Untuk Membangun Program Training Yang Efektifunclassified
“…Bahkan disiplin yang tinggi mencerminkan kesungguhan diri di dalam memperjuangkan tujuan-tujuan perusahaan. Riset yang dilakukan oleh Malau, et al menegaskan, keberhasilan perusahaan sejak awal terlihat dari seberapa disiplinnya para pegawai [12]. Maksudnya, pola kerja teratur dan konsisten memungkinkan pekerjaan terselesaikan tepat waktu, hasil pekerjaan sesuai SOP, memberikan kepuasan kepada stakeholder, dan terciptanya efektivitas.…”
Section: Pendahuluanunclassified